Influence of Ni nanoparticle on the morphology and growth of interfacial intermetallic compounds between Sn-3.8Ag-0.7Cu lead-free solder and copper substrate - Tay, S.; Haseeb, A.; Johan, M.; Munroe, P.; Quadir, Md Zakaria (ELSEVIER Ltd, 2013)
This paper reports on the effects of adding Ni nanoparticles to a Sn-3.8Ag-0.7Cu solder. The nanocomposite was prepared by manual blending of SAC solder paste with various percentages of Ni particles. Results showed that the addition of Ni nanoparticles did not bring any significant change in the onset melting temperature of the solder. An increase in the weight percentage of nanoparticles in the solder caused an increase of the wetting angle and a decrease of spreading rate. Moreover, the addition of Ni nanoparticles changed the interfacial intermetallic compound morphology from a scalloped structure into a planar type structure, enhanced the growth of (Cu,Ni)6Sn 5 and suppressed that of Cu3Sn. The concentration of Ni in (Cu,Ni)6Sn5 was higher at the solder side compared with the substrate side. No nickel was detected in the Cu3Sn phase. Ni nanoparticle additions caused an increase in the interdiffusion coefficient in (Cu,Ni)6Sn5, but a reduction in Cu3Sn. All these effects found in the Ni nanoparticle doped solder are similar to the case when Ni is added as an alloying element. Hence, it is suggested that Ni nanoparticles dissolve into the molten solder and influence the intermetallic compound formation through conventional alloying effects.